One-Pot Selective Synthesis of Multisubstituted Quinoxalin-2(1H)-ones by a Ugi 4CR/Catalytic Aza-Wittig Sequence - Yan, Yan-Mei; Li, Hao-Yang; Ren, Jing; Wang, Song; Ding, Ming-Wu (Synlett, 2018)
A facile, one-pot synthesis of multisubstituted quinoxalin-2(1H)-ones via a Ugi 4CR/catalytic aza-Wittig sequence has been developed. In the presence of a catalytic amount of 3-methyl-1-phenyl-2-phospholene 1-oxide, the reaction of 2-aminobenzoyl azides, aldehydes, ketoacids, and isocyanides selectively produces quinoxalin-2(1H)-ones as the sole products in high yields.
Keywords: quinoxalin-2(1H)-ones; 2-aminobenzoyl azide; Ugi reaction; catalytic aza-Wittig reaction